Karakteristik Subsemiring Fuzzy - Abdurrahman, Saman (Jurnal Fourier, 2020)
Dalam tulisan ini, didefinisikan subsemiring fuzzy dan menyelidiki sifat yang terkait. Selain itu, diperkenalkan konsep subsemiring yang diinduksi dari level subset. Akhirnya, karakteristik subsemiring fuzzy diperoleh. [In this paper, we define the notion of fuzzy subsemiring and investigate the related properties. Moreover, we introduce the idea of a subsemiring induced from the level subset. Finally, a characterization of a fuzzy subsemiring is obtained.]